(untitled) (Journal of Scientific Research, 2012)
Jute, the pride of Bangladesh, has gained interest in the composite field due to its superior specific properties compared to artificial manmade fibers like glass, kevlar, etc. In this study, jute composites made with the vacuum assisted resin infiltration (VARI) techniques were investigated. Jute fiber preform stacking sequences were (0/0/0/0), 0/+45°/-45°/0 and 0/90°/90°/0. For all cases, a total of 25% volume fraction of jute fiber was incorporated. The developed composites were characterized by tensile tests and the experimental results thus obtained were compared with that of the theoretical values. After tensile tests, fracture surfaces were cut and observed under high resolution FEG SEM. In the case of 0/0/0/0 and 0/+45°/-45°/0 lamina composites, longitudinal tensile strength has been found to be higher than that of the transverse direction. However, for 0/90°/90°/0 lamina composites, tensile strengths in both directions were very close to each other. For all developed composites, experimental results revealed that the tensile properties of the developed composites strongly depend on the tensile strength of jute fiber and that the tensile properties of jute fiber are very much defect-sensitive. Finally, a discussion of the tensile behaviors of the composites is initiated in terms of the fracture morphologies observed under the SEM. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.10519 J. Sci. Res. 5 (1), 43-54 (2013)